Legal Regulation of Issues of Intellectual Power Created by Artificial Intelligence: Analysis of the Legislation of Ukraine and UK - Tymoshenko, Olena; Yanishevska , Kateryna; Lytvynenko, Yevheniia; Kravchenko, Ivan (Law, State and Telecommunications Review, 2025)
[Purpose] The article is devoted to a review and comparative analysis of the legislation of Ukraine and UK in the search for common and different approaches to the legal regulation of intellectual property created by artificial intelligence (AI). The study also analyzes the legal status of intellectual property created with the help of AI, evaluates the relevance of legislative acts and the need for changes through the prism of Ukraine's reception of Great Britain's approaches. In addition, the article aims to implement and develop proposals for improving legal regulation, discuss the ethical and legal implications of intelligent AI products, and, finally, form recommendations for further research in the context of regulating the intellectual power of AI based on the analysis of the legislation of both countries. [Methodology/approach/design] The study employs a wide methodological toolkit—analysis and synthesis, comparative legal method, and structural-functional method—to examine similarities and differences in the regulation of intellectual property rights (IPR) and intellectual power in Ukraine and the UK. Comparing these systems is valuable for analyzing economic potential, competitiveness, legal improvement, and knowledge economy development. In the global economy, countries prioritize building intellectual power. The UK’s knowledge economy significantly contributes to its GDP, while Ukraine, though possessing potential, needs stronger mechanisms for IPR protection and commercialization. The UK's developed legal system provides successful examples Ukraine could adapt to boost competitiveness. A robust IPR framework directly impacts investment attractiveness; the UK attracts investors due to reliable innovation protection, a model Ukraine should emulate to enhance its investment climate. Intellectual property also drives innovation, and the UK's public and private initiatives to commercialize research offer lessons for Ukraine. Moreover, the comparison helps assess Ukraine’s legislative progress toward European integration, learning from the UK's experiences within and outside the EU. Overall, this analysis identifies strategic directions for strengthening Ukraine’s IPR system, enhancing innovation protection, and improving economic competitiveness. [Findings] The differences between the Anglo-American and Romano-German legal families, to which Great Britain and Ukraine belong, respectively, dictate the difference in the interpretation of the concepts of "intellectual property rights" and "intellectual power". It is expedient for Ukraine to pay attention to the approaches of legislative regulation of developments created with the help of intellectual activity - first of all, with the aim of protecting the rights of product developers (authors).